2016
DOI: 10.1016/j.hrthm.2015.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Long-term clinical outcomes of focal impulse and rotor modulation for treatment of atrial fibrillation: A multicenter experience

Abstract: BACKGROUND New approaches to ablation of atrial fibrillation (AF) include focal impulse and rotor modulation (FIRM). Studies of this technology with short-term follow-up have shown favorable outcomes. OBJECTIVE The purpose of this study was to characterize the long-term results of FIRM ablation in a cohort of patients treated at 2 academic medical centers. METHODS All FIRM-guided ablation procedures (n = 43) at UCLA Medical Center and Virginia Commonwealth University Medical Center performed between Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
134
2
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(147 citation statements)
references
References 23 publications
6
134
2
2
Order By: Relevance
“…New ablation targets include among others complex fractionated atrial electrograms, additional linear lesions sets, homogenization of atrial fibrosis, modulation of the autonomic nervous system, left atrial appendage isolation, and targeting electric rotors from invasive and noninvasive mapping. The initial results of rotor-guided ablation approaches are heterogeneous, 30,31 and the idea to ablate electric rotors needs further validation. 32 In addition, Akoum et al 29,33 recently reported their interesting ablation approach to target preprocedural fibrosis in patients with PERS.…”
Section: Clinical Implicationmentioning
confidence: 99%
“…New ablation targets include among others complex fractionated atrial electrograms, additional linear lesions sets, homogenization of atrial fibrosis, modulation of the autonomic nervous system, left atrial appendage isolation, and targeting electric rotors from invasive and noninvasive mapping. The initial results of rotor-guided ablation approaches are heterogeneous, 30,31 and the idea to ablate electric rotors needs further validation. 32 In addition, Akoum et al 29,33 recently reported their interesting ablation approach to target preprocedural fibrosis in patients with PERS.…”
Section: Clinical Implicationmentioning
confidence: 99%
“…This may reflect mapping of the epicardium in these studies, where drivers are less stable on optical maps. 7,34 Third, AF-driver ablation outcomes are disappointing at some centers [41][42][43] (Table 1 summarizes PVI and driver ablation studies). Mapping differences will alter reported AF mechanisms, and Rudy et al…”
Section: Reconciling Differences Between Mapping Studies Of Af Rotatimentioning
confidence: 99%
“…However, while independent centers continue to report positive results, 11,12,54,55 outcomes are disappointing by some operators [41][42][43] (Table 1). Table 1 details the heterogeneity in outcomes from map-guided AF source ablation across centers.…”
Section: Reconciling Heterogeneity In the Success Of Source-guided Abmentioning
confidence: 99%
“…18 It is also possible that proarrhythmia develops from small channels or gaps ablation outcome. 51 The Bourdeaux group 52 used an array of 252 body surface electrodes and noncontrast computed tomography scan to obtained accurate biatrial geometry. They found that in the early months of persistent AF it is predominantly maintained by unstable reentry drivers with meandering, and periodic occurrence, also different from Narayan's temporary stable rotors.…”
Section: Rotor Ablationmentioning
confidence: 99%